Pengaruh Iklim Organisasi, Motivasi Kerja Dan Perilaku Inovatif Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Pasuruan - Dyah Arum Widyasari; Mufidah , Eva; Fibriyan, Vita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The purpose of this study was to analyze the relationship between organizational climate and employee performance, work motivation and employee performance, innovative behavior and employee performance. This research method is quantitative. The data collection technique in this study used an online questionnaire technique designed using a Likert scale of 1 to 5 and distributed to 43 employees at the Investment and One-Stop Services Office of Pasuruan City who were selected by purposive sampling method. This data processing tool is SPSS (Statistical Package for Social Science). Before conducting data analysis, first tested the validity and reliability of the questionnaire used. To measure its validity, the score of each question item is used which is correlated with the total item score in one variable. After testing the validity and reliability, then performed data analysis. Analysis and interpretation of data is carried out to answer the problems that have been formulated and answer the hypotheses.